Effects of ethanol on the anticancer function of doxorubicin in JJ012 cells. (18th May 2018) - Huang, Hui; Li, Yanze; Wu, Mingjuan; Luo, Jing; Nie, Junhui; Hou, Baoyu; He, Qi; Diao, Yan; Qi, Lin; Zhao, Yuanyuan; Liu, Ying; Yang, Dan; et al.
Aim: Chondrosarcoma is difficult to treat because of resistance to conventional chemotherapy and radiotherapy. This study evaluated the effects of ethanol in combination with doxorubicin in chondrosarcoma cells.Materials & methods: JJ012, was treated with doxorubicin alone or in combination with ethanol. Effects on cellular proliferation, migration, invasion, apoptosis, and the cell cycle were evaluated.Results: Treatment of JJ012 cells with 100 mM ethanol and doxorubicin resulted in reduced cell growth, invasion, and migration. In addition, doxorubicin uptake into the nucleus was enhanced and p53 mRNA expression was upregulated in JJ012 cells.Conclusion: Ethanol combined with doxorubicin increased doxorubicin uptake in the nucleus and enhanced the effects of doxorubicin in JJ012 cells.